简·爱 ebook Jane eyre. - Brontë, Charlotte (Bridge Bilingual Classics., 2015)
Jane Eyre is an influential novel by English writer Charlotte Brontë. It was published in London, England, in 1847 by Smith, Elder & Co. The novel merges elements of three distinct genres. It has the form of a Bildungsroman, a story about a child's maturation, focusing on the emotions and experiences that accompany growth to adulthood. It is a novel often considered ahead of its time due to its portrayal of the development of a thinking and passionate young woman who is both individualistic, desiring for a full life, while also highly moral. Jane evolves from her beginnings as a poor and plain woman without captivating charm to her mature stage as a compassionate and confident whole woman. As she matures, she comments much on the complexities of the human condition. Jane also has a deeply pious personal trust in God, but is also highly self-reliant. Although Jane suffers much, she is never portrayed as a damsel in distress who needs rescuing. For this reason, it is sometimes regarded as an important early feminist novel. 《简·爱》是一部具有浓厚浪漫主义色彩的现实主义小说。小说主要描写了简·爱与罗切斯特的爱情。主人公简·爱是一个心地纯洁、善于思考的女性，她生活在社会底层，受尽磨难。但她有倔强的性格和勇于追求平等幸福的精神。小说以浓郁抒情的笔法和深刻细腻的心理描写，引人入胜地展示了男女主人公曲折起伏的爱情经历，歌颂了摆脱一切旧习俗和偏见，扎根于相互理解、相互尊重的基础之上的深挚爱情，具有强烈的震撼心灵的艺术力量。